Effect of solid solution treatment on microstructure, tensile properties and residual stress of selective laser melted AlSi10Mg alloy - TANG Pengjun; YAN Taiqi; CHEN Bingqing; GUO Shaoqing; LI Peiyong (Cailiao gongcheng, 2024)
The influence of solid solution treatment on microstructure, tensile properties and residual stress of AlSi10Mg alloy prepared by selective laser melting was investigated by optical microscope, field emission scanning electron microscope, transmission electron microscope, tensile tests and Raman spectrometer. The results indicate that the as-built alloy has a fine microstructure and high strength, but there is obvious anisotropy and significant residual tensile stress. Both the ultimate tensile strength and the yield strength can be improved significantly by direct artificial aging treatment for as-built alloy. However, the morphologies of molten pools and eutectic silicon of aged alloy are as basically same as that of as-built alloy. The solid solution treatment can remarkably improve the anisotropy of microstructure and tensile property, and completely eliminate the residual tensile stress. Meanwhile, it also leads to structural coarsening, resulting in the ultimate tensile strength and yield strength are only about 50% of as-built alloy. For the solid solution treated alloy, there is no obvious change of microstructure, anisotropy and residual stress after artificial aging treatment. The ultimate tensile strength and yield strength reach 330 MPa and 270 MPa respectively, with the elongation after fracture about 10%-11%. The improvement of strength after artificial aging treatment is attributed to the precipitation of GP zone.